Pengaruh Iklim Organisasi terhadap Kepuasan Kerja dan Kinerja Pegawai (Studi pada Kantor Kementerian Agama Kabupaten Kolaka) - Almansyah Rundu Wonua; Ismanto Ismanto; Magefira Rahmadani (Lokawati : Jurnal Penelitian Manajemen dan Inovasi Riset, 2023)
This study aims to determine: (1) The effect of Organizational Climate on Job Satisfaction Employee at Kolaka District Religious Ministry Oficce, (2) The Effect of Organizatonal Climate on Employee Performance at Kolaka District Religious Ministry Office, (3) The Effect of Job Satisfaction on Employee Performance at Kolaka District Religious Ministry Office. This research uses a quantitative method approach. Data collection in this study used observation, documentation and questionnaires. The population of this study were all ASN employees at Kolaka District Religious Ministry Office. While the sample of this study amounted to 41 employee by determining the sample using the census technique. Testing of research instruments using validity tests and reliability tests with SPSS 22.0. The data analysis technique used in this research is Structural Equation Modeling (SEM) based on Partial Least Square (PLS) through measurement model testing (outer model) and structural model testing (inner model) with Smart PLS 4.0. Based on the results of the study, it is known that the Organizational Climate variable has a positive and significant effect on Job Satisfaction as indicated by the P-Values value of 0.012. And the Organizational Climate variable has a positive and significant effect on Employee Performance as indicated by the P-Values value of 0.030. And the Job Satisfaction variable has a positive and significant effect on Employee Perfomance as indicated by the P-Values value of 0.000.